Proceedings of IADC/SPE Drilling Conference 2004
DOI: 10.2523/87127-ms
|View full text |Cite
|
Sign up to set email alerts
|

Novel Drilling Fluid for Through-Tubing Rotary Drilling

Abstract: fax 01-972-952-9435. AbstractThrough-Tubing Rotary Drilling (TTRD) is a technique which has been developed to extend the production life of older fields by substantially reducing drilling costs to render smaller reserves of oil economically recoverable 1 . However, the small wellbore dimensions required to utilise drill-pipe inside production tubing place some unusual demands on the drilling fluid and when these are compounded by the challenges of drilling into a formation containing a large range of pressures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2004
2004
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Field applications of the oil-based drill-in fluid utilizing Mn 3 O 4 showed maximum expected production and formation damage was not significant. 8 The use of Mn 3 O 4 weighting solid in water-based drill-in fluids might lead to good results similar to the oil-based drill-in fluids application. Therefore, this study will investigate water-based drill-in fluids using Mn 3 O 4 particles as weighting materials.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Field applications of the oil-based drill-in fluid utilizing Mn 3 O 4 showed maximum expected production and formation damage was not significant. 8 The use of Mn 3 O 4 weighting solid in water-based drill-in fluids might lead to good results similar to the oil-based drill-in fluids application. Therefore, this study will investigate water-based drill-in fluids using Mn 3 O 4 particles as weighting materials.…”
Section: Introductionmentioning
confidence: 99%
“…The low plastic viscosity associated with Mn 3 O 4 was a result of lower friction in particle to particle interaction due to their spherical shape. 8 Mn 3 O 4 was used with potassium formate brine to drill Gultakes reservoir. Gultakes reservoir has high permeability and small difference between pore pressure and fracturing reservoirs.…”
Section: Introductionmentioning
confidence: 99%
“…• Low ECD (achieved through low viscosity) • Low solids settling tendency (achieved through high viscosity) Two major drilling fluid service companies have solved these requirements differently, but the results are the same; by applying weight material with small particle size both rheology and sagging tendency have been improved compared with conventional mud systems 6,7 . Formate mud, where density is achieved through soluble salts and not through solids is an attractive alternative but its high cost may limit its application 8 .…”
Section: Drilling Fluids Selectionmentioning
confidence: 94%
“…Manganese tetroxide has been used in several drilling operations where advantage was taken of its fine particle size to formulate fluids with relatively low rheology for TTRD (through tubing rotary drilling) applications. 4,5,6 The rheological properties of the above polymers, when dissolved in fresh water, were investigated by Gemma et al 7 They examined the effects at concentrations that would be used in a fully formulated drilling fluid. They observed that polyvinylpyrrolidone, when used on its own, has a weak viscosifying effect with a Newtonian character.…”
Section: Chemistrymentioning
confidence: 99%